THE EFFECT OF FINANCIAL RATIO ON FINANCIAL DISTRESS IN PREDICTING BANKRUPTCY - Joko Supriyanto; Arif Darmawan (Pusat P2M Politeknik Negeri Batam, 2018)
This study was conducted to investigate Financial Distress in mining companies listed on the Indonesian Stock Exchange (BEI) during the 2011-2014 period using the Altman Z-Score Modification. Total sample that gathered from mining companies is 119 companies, analytical techniques used in this study is the Altman Z-score that consists of four ratios, which are the Net Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Tax to Total asset (X3), Market Value of Equity to Book Value of Debt (X4.). This test used SPSS 22 to test the hypothesis, the hypothesis testing results are: Net Working Capital to Total Assets has a positive effect on Financial Distress, Retained Earnings to Total Assets has a positive effect on Financial Distress, Earnings Before Interest and Tax to Total Assets has a positive effect on Financial Distress, Book Value of Equity to Total Liabilities has a positive effect on Financial Distress. This study only used mining companies sector, the further research is recommended to use the other sector companies that have larger numbers of samples.